Literacy : helping students construct meaning - Cooper, J. David; Kiger, Nancy D.; Robinson, Michael D.; Slansky, Jill Ann. (Australia : Cengage, 2018)
A leading resource for K-8 literacy programs, this extremely popular reading methods text has a simple goal: to provide aspiring teachers with the tools to help every student learn to read and write. LITERACY: HELPING STUDENTS CONSTRUCT MEANING, 10th Edition has been completely reorganized to better meet the changing needs of college and university instructors; for instance, with early coverage of assessment in recognition of its foundational nature. This text continues to provide pre-service and in-service teachers with the information, strategies, and techniques they need to assist their students in becoming literate. It is distinguished in the field by its use of practical literacy lessons and authentic examples of children's literature, which clearly demonstrate how to teach reading and writing. The Common Core State Standards are also fully integrated throughout the text, and full-color children's stories (in excerpts or in their entirety) model extended literacy lessons.--publisher.
Includes bibliographical references and indexes.
Keywords: Reading comprehension; Reading; Language arts (Elementary)